THE DEVELOPMENT OF INNOVATIVE-DICK-CAREY TRAINING MODEL TO IMPROVE BIOLOGY TEACHER PERFORMANCE IN APPLYING ICT AT THE STATE SENIOR HIGH SCHOOLS IN SEMARANG CITY - -, Kustiono; Ekosiswoyo, Rasdi; Mantja, Willem; -, Soesanto (Universitas Negeri Semarang, 2013)
Learning condition and situation at schools now need severe teachers performance so that they are not out of date in applying ICT for the sake of education. The application of ICT in education will only be slogan and rhetoric if there are no any serious actions. One of them is the teacher should be a front guard/starter at school. The research problems: (1) how is the grand design of the developed ICT training? (2) how is the effectiveness of the development result-model?. The research findings: (1) the developed ICT training model design is the Innovative Dick-Carey (IDC) modelÃ‚Â which is developed by combining Dick-Carey, BPTKIP, and LPMP models, (2) as the final model result, through the t-test, the IDC training model is very effective to improve teachers performance in learning process. It is suggested that every school should provide educational infrastructures which can give more chances to ICT to be implemented in learning process.